Implementasi Cloud Computing dengan Google Colaboratory pada Aplikasi Pengolah Data Zoom Participants - Gabriel Irfon Elrohi Soen; Marlina Marlina; Renny Renny (JITU : Journal Informatic Technology And Communication, 2022)
Since COVID-19 pandemic, many activities in the world of education, business, and religion, have become online. One of the online video conferencing applications that is often used is Zoom meeting. Due to the lockdown imposed by the government, the use of this application has increased. Even though the paid version has been used, there are still some difficulties for users to know the contributions of participants in meetings via Zoom Meetings, namely to know the data on the duration of participants’ attendance who attend meetings via Zoom and to sort out whether participants attend this meeting from beginning to end. Likewise, if the Zoom recording is stored on a computer or smartphone, it can be lost at any time due to various things. This problem can be solved by using Cloud Drive as the data repository and adding a python script to Google Colaboratory, so it can produce an application that can monitor the activity of each participant in the zoom participant data. After the implementation of the Google Colaboratory at ROCK church Makassar and by taking zoom data for 1 year, the results of the Google Colaboratory platform for the zoom participant data application, produce 3 graphs; a duration graph containing name and time duration data, a join leaves time detail graph containing data on names and hours of entry and exit, and a graph of the number of participants per session rundown of events. Additionally, by using this Google Colaboratory, storage becomes easier because it only requires internet, browser, and email.